O MÉTODO VER-JULGAR-AGIR: GENEALOGIA E SUA RELAÇÃO COM A TEOLOGIA DA LIBERTAÇÃO (Razão e Fé, 2021)
The method Ver-Julgar-Agir emerged asan attempt by Joseph Cardjin to respond tothe harsh reality in which the workers of hiscity, especially the young people, were inserted.Cardjin noticed that the church is far from thereality of the workers, so much so that when hewas a seminarian and returned to his parents’house during the vacation, he realized that,although he was the same age as his friends, hefelt displaced from that social context. In order toface this desire, in the mid 1920’s, Priest Cardjinorganized groups of young workers, inspiredby his own methodology. A few decades later,on the Latin American continent, the desire toproduce a theological reflection less dependenton European schemes and with the face andsmell of the people on this ground emerged: apractical theology. Named Liberation Theology,this system incorporated the method Ver-Julgar-Agir, transforming itself into an epistemic set.